Analiza raziskav gibalne dejavnosti slovenskih osnovnošolskih otrok v zadnjih letih - Strniša, Klavdija; Čagran, Branka (Revija za elementarno izobraževanje, 2015)
Analysis of Research in Physical Activities of Slovenian Basic School Children in Recent Years. Nowadays, physical activity is an extremely important segment of a healthy lifestyle not only for children but also for adults. Technological advances allow us to reach our goals with much less physical effort than was required of the individual in the past. Additionally, the fast pace of life and an increasingly sedentary lifestyle also contribute to reduced physical activity among the population. Analysis of published scientific articles in the field of physical activity among basic school students includes 15 research studies. They were included regardless of the origin of the publication and citation frequency. It can be seen that the most common segment of research in children’s physical activity is the gender perspective. Researchers are further interested in the effects of age, educational success, BMI, place of residence, frequency and time spent in physical activity, education and physical activity of parents, as well as the level of organization (organized / unorganized) activity. Therefore it can be concluded that children’s physical activities are influenced by external and internal factors. Analysis of published research has shown that physical activity depends upon many internal and external factors. A higher level of physical activity is often detected with boys and children in urban areas, compared to rural ones. Physically active parents have physically more active children. A higher proportion of interviewed basic school students was found to participate in organized forms of exercise in comparison to the unorganized ones.
Keywords: basic school students; physical activity; aspects of studying physical activity